MR Evaluation of Large Intracranial Aneurysms Using Cine Low Flip Angle Gradient-Refocused Imaging - Tsuruda, Jay S.; Halbach, Van V.; Higashida, Randall T.; Mark, Alexander S.; Hieshima, Grant B.; Norman, David (American Journal of Neuroradiology, 1988)
MR imaging has proved to be useful in evaluating large intracranial aneurysms. The parent artery and patent lumen can be identified as flow voids and differentiated from thrombus. However, in the presence of slow flow, even-echo rephasing, and motion artifact, increased intraluminal signal may be present, which may be difficult to distinguish from thrombus. Aneurysms are also dynamic lesions and exert pulsatile mass effect on adjacent structures. Further definition of vascular anatomy and physiology may aid in therapeutic planning and assessment. Cine MR is a new technique using a movie loop of sequential GRASS (gradient-recalled acquisition in the steady state) images obtained during various pOints in the cardiac cycle. The combination of GRASS images and cardiac gating thus allows cinegraphic display of vascular structures. A comparison of this method with routine T1- and T2-weighted MR imaging and angiography was made in a group of 13 patients with intracranial aneurysms greater than 1.5 cm in diameter. Eight of these patients underwent transvascular detachable balloon occlusion. With cine MR, flowing blood has high intensity due to flow-related enhancement. Turbulent and high-velocity flow can be recognized on the basis of signal loss, which occurs during systole. Thrombus demonstrated variable signal intensity, which remained unchanged during the cardiac cycle. Compared with routine MR sequences, there was less image degradation from phase-encoding artifacts and improved visualization of the neck of the aneurysm. Pulsatile mass effect was uniquely assessed. After transvascular embolization, cine MR demonstrated improved conspicuity of acute thrombus and higher contrast between flowing blood and the occlusion balloon when compared with routine MR. Confirmation of flow within the parent vessel, residual aneurysm lumen, and distal arterial branches is possible. If the parent vessel was occluded, cine MR yielded greater information than angiography. Cine MR provides additional anatomic and physiologic data in the evaluation and assessment of therapy of intracranial aneurysms. Information can be obtained that is not available with either routine MR or angiography. The inherent limitations of this new technique include partial-volume artifacts, less than optimal flow-related enhancement or spatial resolution, and poor data acquisition due to cardiac arrhythmias.